Tsantan Sumtang attenuated chronic hypoxia-induced right ventricular structure remodeling and fibrosis by equilibrating local ACE-AngII-AT1R/ACE2-Ang1-7-Mas axis in rat. (25th March 2020) - Dang, Zhancui; Su, Shanshan; Jin, Guoen; Nan, Xingmei; Ma, Lan; Li, Zhanqiang; Lu, Dianxiang; Ge, Rili
Abstract: Ethnopharmacological relevance: Tsantan Sumtang, which consists of Choerospondias axillaris (Roxb.) Burtt et Hill, Myristica fragrans Houtt and Santalum album L, is a traditional and common prescription of Tibetan medicine. Tsantan Sumtang originates from Four Tantra with properties of nourishing heart and has been used as a folk medicine for cardiovascular diseases and heart failure in Qinghai, Tibet and Inner Mongolia. Our previous studies found that Tsantan Sumtang showed beneficial effects on right ventricular structure in hypoxia rats, while the underling mechanism remains unclear. Aim of the study: To elucidate the underlying mechanisms of Tsantan Sumtang attenuated right ventricular (RV) remodeling and fibrosis of chronic hypoxia-induced pulmonary arterial hypertension (HPAH) rats. Materials and methods: Fifty male Sprague Dawley (SD) rats (170 ± 20 g) were randomly divided into control group, hypoxia group, and hypoxia + Tsantan Sumtang groups (1.0 g· kg −1 ·day −1, 1.25 g· kg −1 ·day −1, 1.5 g ·kg −1 ·day −1 ). Rats in the hypoxia group and hypoxia + Tsantan Sumtang groups were maintained in a hypobaric chamber by adjusting the inner pressure and oxygen content to simulate an altitude of 4500 m for 28 days. The mean pulmonary arterial pressure (mPAP), right ventricle hypertrophy index (RVHI), the ratio of RV weight to tibia length (TL) (RV/TL), heart rate (HR) and RV systolic pressure (RVSP) was determined. Histomorphological assay of RV structure was evaluated by hematoxylin and eosin (HE) staining. RV tissue fibrosis was assessed by collagen proportion area (CPA), collagen I, collagen III and hydroxyproline content. CPA was obtained by picro-sirius red staining (PSR). The expression of collagen I and collagen III were detected by immunohistochemistry and western blotting. The hydroxyproline content was detected by alkaline hydrolysis. In addition, the level of angiotensin II (AngII) and angiotensin 1-7 (Ang1-7) in RV tissue was tested by enzyme-linked immune sorbent assay (ELISA). Protein expression of angiotensin-converting enzyme (ACE), AngII, AngII type 1 receptor (AT1R), angiotensin-converting enzyme 2 (ACE2), Mas receptor (Mas) were determined by immunohistochemistry and western blotting. mRNA level of ACE, AT1R, ACE2, Mas were tested by qPCR. The chemical profile of Tsantan Sumtang was revealed by UHPLC-Q-Exactive hybrid quadrupole-orbitrap mass analysis. Results: Our results showed that RVHI, RV/TL and RVSP were significantly increased in HPAH rat. Furthermore, levels of collagen I, collagen III and hydroxyproline were up-regulated in RV tissue under hypoxia. We found that RV hypertrophy and fibrosis were associated with increased expression of ACE, AngII, AT1R as well as decreased expression of ACE2, Ang1-7 and Mas. RV remodeling and fibrosis were attenuated after Tsantan Sumtang administration by up-regulating ACE2 and Mas level as well as down-regulating ACE, AngII and AT1R levels in RV tissue. 35 constituents in Tsantan Sumtang were identified. Conclusion: Tsantan Sumtang attenuated RV remodeling and fibrosis in rat exposed to chronic hypoxia. The pharmacological effect of Tsantan Sumtang was based on equilibrating ACE-AngII-AT1R and ACE2-Ang1-7-Mas axis of RV tissue in HPAH rat. Graphical abstract: Image 1